A network pharmacological approach to investigate the pharmacological effects of CZ2HF decoction on Alzheimer's disease. Issue 3 (28th September 2021) - Wei, Yu; Gao, Jian‐Mei; Xu, Fan; Shi, Jing‐Shan; Yu, Chang‐Yin; Gong, Qi‐Hai
Abstract : Background: Alzheimer's disease (AD) is the most common type of dementia, which brings tremendous burden to the sufferers and society. However, ideal tactics are unavailable for AD. Our previous study has shown that CZ2HF, a Chinese herb preparation, mitigates cognitive impairment in AD rats; whereas, its detailed mechanism has not been elucidated. Methods: Public databases were applied to collect and identify the chemical ingredients of eight herbs in CZ2HF. Criteria of absorption, distribution, metabolism, and excretion was used to screen oral bio‐availability and drug‐likeness. STITCH database and Therapeutic Target Database were applied to decipher the relationship between compounds and genes related to AD. Kyoto Encyclopedia of Genes and Genomes and Gene Ontology term analyses were used to identify the involved signaling pathways. Cytoscape was adopted to establish the networks The molecular docking was used to validate the interactions between the candidate compounds and their potential targets. Results: 914 compounds were identiﬁed in eight herbal medicines of CZ2HF. Among them, 9 compounds and 28 genes were highly involved in the pathologic process of AD. Furthermore, the mechanism of CZ2HF to AD was based on its anti‐inflammatory effects mainly through lipopolysaccharide‐mediated signaling pathway and TNF signaling pathway. Core genes in this network were TNF, ICAM1, MMP9 and IL‐10. Conclusion: This study predicts the active compounds in CZ2HF and uncovers their protein targets using holistic network pharmacology methods. It will provide a insight into the underlying mechanism of CZ2HF to AD from a multi‐scale perspective.